PENGARUH STRATEGI PQ4R TERHADAP MEMBACA PEMAHAMAN SISWA PADA MATA PELAJARANBAHASA INDONESIA - PUJI RAHMAWATI (Bestari: Jurnal Pendidikan dan Kebudayaan, 2021)
The background of this research is based on direct observation and recap of Indonesian students grades. Known students are weak in reading comprehension, like not being able to write information in reading. The purpose of the study was to find out the effect of the PQ4R strategy on students reading comprehension. Research methods using experimental research. The study was conducted for two days. The number of subjects was 22 students consisting of 8 boys and 14 girls. Data collection was carried out by means of tests in the form of essays totaling 6 items. The results of the study are seen from the average total overall students grade. The first day of the pretest activity scored a value of 50,63 while the second day of the posttest activity scored a value of 58,72. It is known that the first day seen from KKM which is 70 all the grades of students under the KKM then obtained 0% for students who graduate. Then the second day the percentage increased to 14% because there were 3 students out of 22 students who scored above the KKM. Thus it was stated that the PQ4R strategy had an influence although it was not large. Based on the value of the regression coefficients on the output in the coefficients table is sought using the linear regression equation it is know that the regression coefficients value is positive (+), then it can be said that posttest (X) has a positive effect on pretest (Y). So the regression equation is Y = 0,544 X + 18,689.